2005
DOI: 10.1111/j.1471-4159.2005.03511.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency, but not low‐frequency, transcutaneous electrical nerve stimulation reduces aspartate and glutamate release in the spinal cord dorsal horn

Abstract: Transcutaneous electrical nerve stimulation (TENS) is a commonly utilized non-pharmacological treatment for pain. Studies show that low-and high-frequency TENS utilize opioid, serotonin and/or muscarinic receptors in the spinal cord to reduce hyperalgesia induced by joint inflammation in rats. As there is an increase in glutamate and aspartate levels in the spinal cord after joint inflammation, and opioids reduce glutamate and aspartate release, we hypothesized that TENS reduces release of glutamate and aspart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 41 publications
3
60
1
5
Order By: Relevance
“…The differential changes in extracellular GABA concentrations in response to low and high frequency TENS has been shown previously for other neurotransmitters and receptors (Sluka et al, 1999;Kalra et al, 2001;Sluka et al, 2005Sluka et al, , 2006. Specifically, in the spinal cord serotonin is increased in response to low frequency TENS, but not high frequency TENS.…”
Section: Neurotransmitter Mechanisms Of Tenssupporting
confidence: 55%
“…The differential changes in extracellular GABA concentrations in response to low and high frequency TENS has been shown previously for other neurotransmitters and receptors (Sluka et al, 1999;Kalra et al, 2001;Sluka et al, 2005Sluka et al, , 2006. Specifically, in the spinal cord serotonin is increased in response to low frequency TENS, but not high frequency TENS.…”
Section: Neurotransmitter Mechanisms Of Tenssupporting
confidence: 55%
“…While low-frequency TENS acted via mu opioid receptors, high-frequency TENS acted via activation of delta opioid receptors, subsequently reducing the increased release of glutamate and aspartate in the spinal cord receptors. [44][45][46] However, a recent systemic review concluded based on an analysis of previous twenty studies that the pulse frequency of TENS didn't influence clinical analgesic effect as long as its pulse intensity, pulse pattern, and pulse duration were constant. 23) A previous study showed that both frequency-modulated TENS and constant-frequency TENS were superior in analgesic effect to placebo TENS but the modulation of pulse frequency did not increase hypoalgesia.…”
Section: Pulse Frequencymentioning
confidence: 99%
“…The group receiving cryotherapy alone did not show significant pain relief at final evaluation as compared to initial evaluation (p > 0.05). However, when comparing pain at final evaluation among groups, there has been no significant difference in the improvement obtained with the protocols used (p > 0.05) 10 . So, such results are in agreement with our study, contrasting only with regard to the cryotherapy group, where our study has evidenced significant pain relief, maybe due to the difference in methodology to induce analgesic technique, which in our study was during 5 days, with 1 session per day, and in the other study it was 2 sessions per week during 4 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…In the muscle, it decreases triggering speed of I A fibers of the muscle spindle, decreasing spasm 8 . Different theories were proposed to explain TENS action mechanism, however, the most widely accepted it the Theory of Pain Floodgate Control, according to which nociceptive information competes with nervous fibers transmitting artificial electric stimulations generated by TENS to upper centers, modulating painful information in segmental and subsegmental areas of the central nervous system 9,10 . A different theory proposed to explain TENS action mechanism is through the activation of inhibitory pain pathways, of periaquedutal and raphe nucleus gray matter, which originate in the brain and descend to the spinal cord through brain stem, releasing endogenous opioids 4 .…”
Section: Discussionmentioning
confidence: 99%